Manajemen Strategik Pembelajaran Pondok Pesantren dalam Mewujudkan Generasi yang Berakhlaqul Karimah - Ummu Khurriyah; Eliyanto Eliyanto (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
This research is motivated by the importance of Islamic boarding schools in realizing a generation of good morals. This study aims to reveal the strategic management of Islamic boarding school learning in realizing a generation with good morals at the Al-Kamal Tambaksari Islamic Boarding School, Kuwarasan District, Kebumen Regency. The approach used in this study is a qualitative case study. The research subjects were determined by purposive sampling technique, which consisted of the Chairperson of the Islamic Boarding School Board of Directors, the Head of the Islamic Boarding School Early Childhood School, and the Islamic Boarding School Ustadz. Research data were collected through in-depth interviews, participant observation, and document analysis. The research data were analyzed using interactive analysis techniques developed by Miles & Huberman, namely: data reduction, data presentation, and drawing conclusions. This research shows three guests. First, the strategic planning of learning for Islamic boarding schools in creating a generation of good morals at Al-Kamal Tambaksari Islamic Boarding School, Kuwarasan District, Kebumen Regency is by formulating each existing program, the leadership of the Islamic boarding school always formulates and holds deliberations with the asatidz council and all existing stakeholders to equalize the vision, mission and steps to achieve it. Second, the strategic implementation of Islamic boarding school learning in realizing a generation of good morals at the Al-Kamal Tambaksari Islamic Boarding School, Kuwarasan District, Kebumen Regency is carried out in stages and in an organized manner, always accompanied by the leadership of the Islamic boarding school, surveyed for its activities and intense mentoring, as well as an open leadership model. Third, strategic evaluation of Islamic boarding school learning in creating a generation with good morals at the Al-Kamal Tambaksari Islamic Boarding School, Kuwarasan District, Kebumen Regency is by: (a) directly observing the behavior of students in everyday life (amaliyah dzahiriyah); (b) evaluations carried out both formally and informally; (c) see directly changes in the behavior of students after receiving coaching; (d) evaluation carried out in weekly, monthly, semi-annual, year-end and early-year evaluation activities; and (e) emergency evaluation.